2018
DOI: 10.1111/apt.14849
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of autoimmune gastritis in patients misdiagnosed with two or more failures of H. pylori eradication

Abstract: AIG patients were often misdiagnosed as refractory to eradication therapy, probably because achlorhydria in AIG might allow urease-positive bacteria other than H. pylori to colonise the stomach, causing positive C-UBT results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
3
36
2
4
Order By: Relevance
“…H pylori infection is also known to be an important cause of atrophy and IM, the premalignant lesion of GC . Although there are other causes of atrophy, such as autoimmune gastritis, we could not find autoimmune gastritis in our institution, which is different from the recently published Japanese study . Instead of rare autoimmune gastritis, most of atrophy was related to H pylori in Korea .…”
Section: Introductioncontrasting
confidence: 96%
“…H pylori infection is also known to be an important cause of atrophy and IM, the premalignant lesion of GC . Although there are other causes of atrophy, such as autoimmune gastritis, we could not find autoimmune gastritis in our institution, which is different from the recently published Japanese study . Instead of rare autoimmune gastritis, most of atrophy was related to H pylori in Korea .…”
Section: Introductioncontrasting
confidence: 96%
“…Some of the patients who underwent treatment were considered to have been incorrectly classified as Hp‐ positive. A previous report suggested that proliferations of urease‐positive bacteria other than Hp under non‐acidic circumstances possibly resulted in positive 13 C‐UBT test results. Thus, such misclassification leads to unnecessary treatment for Hp .…”
Section: Discussionmentioning
confidence: 98%
“…In Japan, the prevalence of AIG was assumed to be very low until about a decade ago . However, possibly on the background of a recent dramatically rapid decrease in Helicobacter pylori ( Hp ) prevalence, reports on AIG are increasing . This multicenter registry study aimed to clarify the characteristics of AIG in Japan and explore its endoscopic appearances.…”
Section: Introductionmentioning
confidence: 99%
“…H pylori infection, an additional risk factor for gastric cancer, must be ruled out by histology and, in case of histological doubts (eg presence of active inflammation in gastric mucosa, development of atrophy in the antrum or incisura angularis), by antigen stool test. In fact, false‐positive urea breath test results are common in AAG, due to hypo‐achlorhydria . Finally, there now seems to be enough evidence to support the follow‐up of PCA‐positive individuals with non‐atrophic gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%